Teacher Competency Analysis in Formulating Higher Order Thingking Skills (HOTS) Based on Critical Thingking Based on 2013 Curriculum To Accelerate Education 4.0 - Mulyono, Hadi; Istiyati, Siti; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Universitas Sebelas Maret, 2019)
The purpose of the service is to train elementary school teachers to have the competency to prepare Higher Order Thingking Skills (Hots) Based on Critical Thingking Based on 2013 Curriculum To Accelerate Education 4.0. In addition to training teachers, this service also aims to analyze teacher competencies in preparing Higher Order Thingking Skills (Hots) Based on Critical Thingking Based on 2013 Curriculum To Accelerate Education 4.0. The subject of this service is an elementary school teacher in the city of Surakarta. The method used in this service starts with Workshop, Practice, and Implementation. In conducting this training, the subjects were asked to take a test related to the preparation of HOTs-based questions. Analysis of the data used is pre-test and post-test. The result of this activity is that there is an increase in the knowledge and understanding of teachers about HOTS-based question preparation